Pelatihan Media Pembelajaran Interaktif Sebagai Upaya Peningkatan Pembelajaran Daring Bagi Guru-guru SDIT Al-Kautsar Cikarang - Achmad Fauzi; Nuraini Purwandari; Rr. Aryanti Kristantini; Hilman Jihadi (ABDIMAS Jurnal Pengabdian Kepada Masyarakat, 2022)
SDIT Al-Kautsar is an Integrated Islamic Elementary School located in Cikarang that carries out online learning in teaching and learning activities during the Covid19 pandemic. The implementation of distance education cannot be separated from the use of technology. This is because in distance education there is no direct contact between teachers and students. The communication process between the two is carried out through the use of communication and information technology. There are many types of applications that support online learning technology. The purpose of this training is to provide basic knowledge to SDIT Al-Kautsar Cikarang teachers about online learning media, namely Google Classroom, Google meet and Zoom meetings so that this SDIT Al-Kautsar school is more developed in terms of information technology.